Biogeochemical Variability of the Upper Ocean Response to Typhoons and Storms in the Northern South China Sea - Shih, Yung-Yen; Hung, Chin-Chang; Huang, Szu-Yu; Muller, François L. L.; Chen, Yu-Hsuan (Frontiers in Marine Science, 2020)
Satellite remote sensing of chlorophyll a (Chl) has produced evidence of typhoon-induced phytoplankton blooms in the tropical and subtropical ocean but it is difficult to evaluate if the particulate organic carbon (POC) fixed by marine organisms can be transported into deep waters. Recent field observations have shown enhancements in primary production, Chl and POC flux associated with the passage of typhoons over the shallow waters (< 200 m) of the continental shelf. However, it is still unclear whether typhoons, which originate beyond the continental margin, can transfer the newly fixed carbon to deeper waters. Here we report on nitrate+nitrite (N), Chl and POC fluxes in the northern South China Sea (NSCS) before and shortly after the passage of typhoons and storms, between September 2012 and June 2014. The integrated inventories of N (0–150 m) 8, 3, 2 and 5 days after passage of typhoons Tembin, Soulik, Knongrey were 0.44, 0.16, 0.36 and 0.48 mol m−2, and these values were not significantly different from inventories of N under normal, non-typhoon conditions (0.18 ~ 0.48 mol m−2). The integrated Chl values 8, 3, 2 and 5 days after passage typhoons Tembin, Soulik, Knongrey were 35, 24, 14 and 28 mg m−2, i.e. lower than Chl inventories when no typhoons occurred (29 ~ 40 mg m−2). POC fluxes after the passage of typhoons Tembin and Soulik were 78 ± 12 and 115 ± 16 mg-C m−2 d−1 (average ± 1 standard deviation), i.e. 1.6 and 2.4 times higher than those obtained before the typhoon. In addition, variations in both surface and depth-integrated Chl were decoupled from POC fluxes. This decoupling may be attributed to a change in the plankton community composition due to water column instability or to lateral inputs of particulate matter released from shelf or slope sediments. Overall, our analysis of this two-year dataset highlights the spatial and temporal variability of the factors controlling POC exports to the deep NSCS.